ENGLISH LANGUAGE SPEAKING ANXIETY AMONG COMMUNITY COLLEGE LEARNERS: HOW CAN IT BE OVERCOME? - Tati, Johan Severinus; Paul, Canne; Golingi, Liza Blasius (PEOPLE: International Journal of Social Sciences, 2016)
Language anxiety is a common phenomenon that most of the language learners have gone through. The level of anxiety varies from person to person. Learners usually become anxious when they are not the native speakers of a particular language, but are required to learn or use the language. Learners demonstrate poor speaking performance because they are not competent with the target language. This study aims to investigate the factors affecting speaking anxiety among the learners, the common factors of anxiety and to observe strategies employed by learners to overcome their fear of speaking the English language. Interviews were conducted with the selected respondents in the Community Colleges in Sabah and Community Colleges in Kedah. The data obtained were transcribed and analyzed using discourse approach. The findings indicated that lack of vocabulary and fear of negative evaluation was the major factors of anxiety in speaking English language. Most learners employed an imitation strategy topractice speaking in English and to reduce the fear of speaking the English language. This study suggests that English teachers are the crucial main motivators to alleviate speaking anxiety and utilizing them in pedagogical context.